A vicious cycle: employment challenges associated with diabetes foot ulcers in an economically marginalized Southwest US sample - Palmer, Kelly N. B.; Crocker, Rebecca M.; Marrero, David G.; Tan, Tze-Woei (Frontiers in Clinical Diabetes and Healthcare, 2023)
Aim To describe patients’ reported employment challenges associated with diabetic foot ulcers (DFUs). Methods Fifteen patients from under-resourced communities in Southern Arizona, with a history of DFUs and/or amputations, were recruited from a tertiary referral center from June 2020 to February 2021. Participants consented to an audio-recorded semi-structured phone interview. Interviews were transcribed and thematically analyzed using the Dedoose data analysis platform. Results Participants shared a common theme around the cyclic challenges of DFU prevention/management and employment. Those employed in manual labor-intensive jobs or jobs requiring them to be on their feet for long durations of time believed working conditions contributed to the development of their DFUs. Patients reported work incapacity due to declines in mobility and the need to offload for DFU management. Many expressed frustration and emotional distress related to these challenges noting that DFUs resulted in lower remuneration as medical expenses increased. Consequently, loss of income and/or medical insurance often hindered participants’ ability to manage DFUs and subsequent complications. Conclusion These data illuminate the vicious cycle of DFU and employment challenges that must be addressed through patient-centered prevention strategies. Healthcare providers should consider a person’s contextual factors such as employment type to tailor treatment approaches. Employers should establish inclusive policies that support patients with DFUs returning to work through flexible working hours and adapted work tasks as needed. Policymakers can also mitigate employment challenges by implementing social programs that provide resources for employees who are unable to return to work in their former capacity.